2000
DOI: 10.1029/2000jb900118
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric instability beneath the Transverse Ranges of California

Abstract: Abstract. Recent high-resolution seismic experiments reveal that the crust beneath the San Gabriel Mountains portion of the Transverse Ranges thickens by 10-15 km (contrary to earlier studies). Associated with the Transverse Ranges, there is an anomalous ridge of seismically fast upper mantle material extending at least 200 km into the mantle. This high-velocity anomaly has previously been interpreted as a lithospheric downwelling. Both lithospheric downwelling and crustal thickening are associated with the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 37 publications
(18 reference statements)
5
86
0
Order By: Relevance
“…The Pacific-North American plate boundary in Southern California is also thought to consist of a highvelocity uppermost-mantle downwelling (Humphreys and Clayton, 1990;Houseman et al, 2000) but no seismicity deeper than 27 km is observed (Richards-Dinger and Shearer, 2000). The regional Southern California average uppermost mantle P-wave velocity is low (Յ7.8 km/sec) (Hadley and Kanamori, 1977;Hearn and Clayton, 1986;Richards-Dinger and Shearer, 1997) implying an environment too warm to enable deep crustal or mantle seismicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pacific-North American plate boundary in Southern California is also thought to consist of a highvelocity uppermost-mantle downwelling (Humphreys and Clayton, 1990;Houseman et al, 2000) but no seismicity deeper than 27 km is observed (Richards-Dinger and Shearer, 2000). The regional Southern California average uppermost mantle P-wave velocity is low (Յ7.8 km/sec) (Hadley and Kanamori, 1977;Hearn and Clayton, 1986;Richards-Dinger and Shearer, 1997) implying an environment too warm to enable deep crustal or mantle seismicity.…”
Section: Discussionmentioning
confidence: 99%
“…Large horizontal and vertical shear strains have been modeled for downwelling mantle lithosphere below converging continents within a two-dimensional slice parallel to the convergent zone (Houseman et al, 2000). The largest (Table 1) are also plotted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the seven dimensionless numbers, the viscosity ratio η 0 affects growth rates, deflections of interfaces, and gravity anomalies most, and past studies with constant viscosity in the layers have considered a range of η 0 from 0.01 to 100, with values near η 0 = 1 seeming to match Earth-like conditions best [Houseman et al, 2000;Molnar and Houseman, 2013;Neil and Houseman, 1999]. We too carried out calculations for five values of η 0 , 0.01, 0.1, 1.0, 10, and 100, but in general, we present results only for η 0 = 0.01, 1.0, and 100.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
“…However, the time scale involved in the convective removal of the mantle lithosphere is uncertain because the viscosity is not well known. Numerical simulations by different authors show that the duration of the removal can vary drastically from 10 Ma to a few hundreds of million years, depending on the rheological parameters in the simulation experiments [Davaille and Jaupart, 1993;Conrad, 2000;Houseman et al, 2000;Morency et al, 2002]. The roughly concurrent onsets of tectonic processes in the surrounding regions have led to the suggestion of a rapid removal of the mantle lithosphere beneath Tibet at about 8 Ma ago [Harrison et al, 1992;Molnar et al, 1993].…”
Section: Introductionmentioning
confidence: 99%